Grape seed extract ameliorates PhIP-induced colonic injury by modulating gut microbiota, lipid metabolism, and NF-κB signaling pathway in rats - Xiuli Zhao; Yuekun Wu; Hengchao Liu; Nan Hu; Yan Zhang; Shuo Wang (Journal of Functional Foods, 2021)
2-Amino-1-methyl-6-phenylimidazo[4,5-b] pyridine (PhIP) is a common carcinogen produced in thermally processed protein-rich foods. This study explored the protective effects of grape seed extract (GSE) against colonic injury induced by short-term exposure to PhIP and the underlying mechanisms involved. Wistar rats were randomly divided into four groups: control, GSE only (GSE), PhIP (PhIP), and GSE prevention (GPhIP). In the GPhIP group, rats were fed a diet supplemented with GSE for 2 weeks before administering PhIP. GSE significantly ameliorated PhIP-induced oxidative stress and colonic DNA damage. Moreover, GSE effectively maintained homeostasis in intestinal flora, especially by preventing PhIP-mediated reduction in Lactobacillus abundance. Fecal metabolome and colonic transcriptome analyses revealed that GSE remarkably ameliorated PhIP-induced colonic injury by regulating lipid metabolic pathways. Notably, nuclear factor-κB signaling pathway involved in the process of prevention. Therefore, GSE is recommended as an effective dietary supplement to prevent the harm of PhIP in vivo.